تحسين أداء أنظمة القيادة التي تعمل وفق مبدأ التحكم السلمي (v/f const) - عطية بسام عبد الله (Latakia University Journal -Engineering Sciences Series, 2019)
يتناول البحث تقييم وتحسين أداء ومردود نظام تحكم سلمي لقيادة محرك تحريضي ثلاثي الطور ذي دائر مقصور(Squirrel Cage Induction Motor)، يعمل في الأرباع الأربعة (four-quadrant operation)، عن طريق تنظيم الانزلاق باستخدام مبدأ تعديل عرض النبضة (pulse width modulation PWM) لمعرج توتر voltage source inverter (VSI) بترانزستورات من نوع IGBT، تعمل على تنظيم كل من التردد والتوتر وفق النسبة V/F=const. لقد تم وضع الخوارزمية الرياضية لنظام القيادة المذكور والتي تشكل حجر الأساس لبرمجة المعالجات والمتحكمات الميكروية المستخدمة في التطبيقات العملية لأنظمة قيادة الروافع والمصاعد، حيث تم وضع شروط التشغيل لنظام القيادة وتصميم مكونات دارة تشكيل إشارات القدح لمفاتيح المعرج وفق مبدأ التعديل الجيبي لعرض النبضة (المتحكم PI- المحدد - متحكم الجهد..)، وبناء على الخوارزمية الرياضية، تم نمذجه النظام باستخدام برنامج simplorer 8. بناءً على الدراسة والتقييم لنتائج النمذجة, تم تحديد سلبيات نظام التحكم السابق و قمنا باقتراح إضافة حلقة تحكم بتيار دخل المعرج بهدف الحصول على خواص أداء أفضل وتحسين مردود النظام عن طريق تخفيض كل من: تيارات الإقلاع والكبح- عوامل تشويه إشارات الجهود والتيارات والعزوم - الاجهادات الكهروميكانيكية الديناميكية في الحالات العابرة (إقلاع - كبح). Our research concentrates on evaluating and improving the performance and the efficiency of adjustable speed Squirrel Cage Induction Motor drives operating in four-quadrant operation, controlling the slip using the pulse width modulation (PWM) of a voltage source inverter that uses IGBTs Transistors for controlling frequency and voltage and maintaining V/F=const. Being fundamental to programming the microprocessors and microcontrollers used in every practical application of the control systems of elevators, lifts etc , The algorithm required for the electrical drives has been stated in our research. We have also defined the operating conditions for the electrical drive system and then designed the parts of the circuit responsible for generating trigger signals that control the function of the inverter switches using the pulse width modulation principal (PI controller – Limiter – Voltage controller , Etc….). And by using the SIMPLORER 8 program (Full version), we could complete the system simulation. Based on studying and evaluatiing the model concerned, we have identified the disadvantages of such a system. So, we have suggested adding a loop DC current control to the inverter input in order to obtain a better performance and system efficiency by reducing start up and braking currents –the factors of distorting the signals of currents, voltages, and torques – and the excess of dynamic electromechanical overloads during transient conditions (start up-brake).